The Future of Mental Health, Disability and Criminal Law Essays in Honour of Emeritus Professor Bernadette McSherry - Wilson, Kay; Maker, Yvette; Gooding, Piers; Walvisch, Jamie (Taylor & Francis, 2024)
This book brings together contributions from twenty-three world-leading scholars and commentators that address a range of contemporary and pressing international themes in mental health, disability and criminal law. The authors use the work of internationally renowned academic, Emeritus Professor Bernadette McSherry, as a springboard to reflect on recent developments in these areas of law and to anticipate the future directions they may take. In doing so, they aim to inform and inspire a new generation of mental health, disability and criminal law scholars, advocates and reformers. The book is divided into four substantive sections: reforming mental health and disability law; regulating coercion and restrictive practices; improving access to justice and the criminal law; and transforming mental health law. It also includes an introduction from the editors and an afterword from Emeritus Professor McSherry. The book is aimed at regulators, policymakers, lawyers, clinicians, consumer advocates and academics who are interested in the urgent and contentious issues surrounding the reform and development of mental health, disability and criminal law. It will help them understand the key issues and problems and presents suggestions for reform. The book is interdisciplinary and international in its focus.